Renal and hepato protective effects of green tea (camellia sinensis) extract on wistar rats treated with sodium oxalate - DEBAJYOTI BHATTACHARYA; MAUSUMI SIKDAR (nee) BHAKTA (International Journal of Pharma and Bio Sciences, 2016)
Nowadays different foods and vegetables are contaminated with oxalates of sodium and calcium, present in pesticides and chemical fertilisers. Even many drugs contain sodium oxalate, which is a causative agent of urolithiasis and hepatic cell damage. Herbal plant supplements may reduce this drug induced toxicity. Renal and hepatoprotective effects of the aqueous extracts of green tea (Camellia sinensis) were studied in sodium oxalate treated rats. Green tea extract was administered orally to Wistar rats for 20 days, exposed to sodium oxalate in different doses (100 mg/kg body weight and 200 mg/kg body weight. It was administered at a dose of 100 mg/kg body weight, which caused hepatic and renal cell damage. As a result, the different stress marker enzyme activity (Aspartate Transaminase, Alanine Transaminase and Alkaline Phosphatase) were increased. Green tea extract have an ameliorative effect on sodium oxalate induced damage and can also reduce the tissue cholesterol level in both liver and kidney.